Simulating nitrate formation mechanisms during PM2.5 events in Taiwan and their implications for the controlling direction. (15th January 2022) - Chuang, Ming-Tung; Wu, Chang-Fu; Lin, Chuan-Yao; Lin, Wei-Che; Chou, Charles C.-K; Lee, Chung-Te; Lin, Tang-Huang; Fu, Joshua S.; Kong, Steven Soon-Kai
Abstract: The long-term downward trend of NOX concentrations does not reflect the reduction of nitrate (NO3 − ) in Taiwan. Instead, the proportion of NO3 − in PM2.5 increased in recent years. To probe the increasing importance of NO3 − in PM2.5, this study applied the WRF/CMAQ modeling system to implement a simulation from 16 March 2017 to 30 April 2017, in which 5 p.m.2.5 events with daily average concentrations ≥35 μg m −3 and their corresponding correlation coefficients (R) of simulated and observed PM2.5 above 0.6 were selected for analysis. During the daytime, the reaction of NO2 and OH contributed more than 90% of the total HNO3 . After sunset, the high concentrations of NO3 and N2 O5 peaked, followed soon by the simultaneous rise of NO3 −, aerosol water content, and HNO3 concentrations around midnight, which indicated that the heterogeneous reaction was the main formation mechanism of NO3 −, accounting for approximately 30%–90% of total HNO3 . At nighttime, the daytime-formed gaseous phase NO3 − condensed, and low wind and low boundary layer height favored accumulation; therefore, PM2.5 peaked around the midnight period to the early morning. The sensitivity test showed that doubling and halving the NOX and NH3 emissions could directly lead to the highest production and reduction of NO3 −, respectively, followed by doubling and halving NMHC emissions, which caused the highest and lowest O3 concentrations. The correlation analysis of the simulation results showed that the daytime maximum O3 and HNO3 were highly correlated. The relationships between daytime maximum O3, nighttime maximum NO3, N2 O5, and HNO3 in pairs were also moderately to highly correlated. This study implies that in addition to direct reduction of NOX or NH3 emissions, controlling O3 is possibly another useful strategy to reduce NO3 − . Because NOX emission reduction could conflict with controlling O3, this study suggests to re-examine the determination of NOX -limited and VOCS -limited regions in order to develop strategies for reducing NOX emission and O3 simultaneously. Graphical abstract: The proportion of NO3 - in PM2.5 was the highest among PM2.5 components in many recent PM2.5 episodes. The daytime NO2 +OH→HNO3 accounts more than 90% of total HNO3 . The nighttime heterogeneous reaction of N2 O5 accounts about 50% to 90% of total HNO3, plus the daytime NO3 - condensed, forms the high NO3 - and high PM2.5 event. The simulation result suggests to control O3 could reduce NO3 - and thus PM2.5 . Image 1 Highlights: The observed proportion of NO3 − in PM2.5 has been decreasing in recent years. Evolution of meteorology, NO3 −, its precursors/intermedia products are addressed. The contributions of eight NO3 − formation pathways were calculated. To control O3 could also reduce NO3 − in addition to direct NOx and NH3 reduction. Daytime maximum O3 has close relationship with daytime/nighttime maximum HNO3 .